A study of the cell morphology and mechanical properties of bumper material PP-T-EPDM composite foam. Issue 2 (March 2023) - Yetgin, Salih Hakan; Unal, Hüseyin
In this study, cellular polypropylene based composite foams were prepared using an universal injection moulding machine. The chemical foaming agent was added to neat polypropylene (PP) polymer, talc filled polypropylene (PP-T) composite and talc filled polypropylene/ethylene-propylene-diene blend (PP-T-EPDM) composite materials at the ratio of 1% and 2% by weight. The influence of foaming agent content on the mechanical and cellular properties of both neat PP polymer and PP composites was investigated. The results showed that the tensile strength, tensile modulus, impact strength, hardness, cell diameter, foam density and viscosity values and skin layer thickness decreased while volume expansion ratio increased with the increment in chemical blowing agent content.